Correction: Light-penetration and light-scattering effects in dye-sensitised solar cells. (13th January 2016) - Hwang, Kyung-Jun; Kim, Dajung; Park, Ju-Young; An, Jongdeok; Jin, Sungho; Kang, Sang Ook; Cho, Dae Won; Im, Chan
Abstract : Correction for 'Light-penetration and light-scattering effects in dye-sensitised solar cells' by Kyung-Jun Hwang et al., New J. Chem., 2014, 38, 6161–6167.